PENGARUH GROWTH DAN FINANCIAL STRENGTH TERHADAP FINANCIAL LEVERAGE - HENNY SETYO LESTARI; FARDINI RAHMA DEWI (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2013)
This study aims to determine the effect of firm’s growth and financial strength towards financial leverage of listed companies on the Indonesia Stock Exchange from 2008-2012. The number of samples examined in this study were 92 companies with the sampling technique used was purposive sampling. The empirical results of this study using by the method of multiple linear regression analysis. The results of the study indicate that the asset growth and profit growth has a positively effect on financial leverage through the total debt to total assets and total debt to equity capital model, but sales growth has no effect on financial leverage. This indicates that the company with assets and profit growth will tend to use financial leverage in funding. This study also shows that financial strength has a negatively effect on financial leverage through the long-term debt to total assets and long-term debt to fixed assets model. This indicates that companies with strong financial aspects tend to reduce long-term debt as a source of funding.